Behind the Charm of Billboards: An Analysis of Social Semiotics of the Propaganda Language of the 2024 Kendari Mayoral Candidates - Rahmawati, rahmawati; Muhammad Hasyim; Yusniati N. Sabata; Andi Muh Ruum Sya’baan; Sulfiah (English Education Study Program, 2024)
This study aims to unveil the charm behind the political campaign billboards for the 2024 Kendari Mayor candidate that use propaganda language through social semiotics analysis. The data used in this study are two billboards from candidates for Mayor in Kendari City in 2024 who have the highest electability survey results or candidates who are popular in the people of Kendari City. This study used a qualitative approach to analyze written text and visual text on billboards. The results showed that the two billboards analyzed had similarities in using propaganda language, such as logos, slogans, background colors, and the color of candidates' clothes. This research shows that the object of billboard participants is used to attract the attention of the audience and that the propaganda language in billboards moves through various elements such as logos, slogans, photo techniques, color composition, image arrangement, background color, and color of the candidate's clothing.